Physicochemical Properties and Sensory Evaluation of Banana Peel Flour Biscuits - Khadijah Syed Abu Bakar, Syarifah; Ahmad, Noorlaila; Jailani, Fadhilah (International Journal of Engineering and Technology, 2019)
Banana peels consist of valuable bioactive compounds and yet remain underutilised. This study investigated the effect of banana peel flour incorporation into biscuit formulation. The physicochemical properties and sensorial acceptability of biscuits produced at the different level of substitution (0%, 10%, 20%, 30% and 40%) of Banana Peel Flour (BPF) were determined. The ash content (1.66% to 2.11%), moisture content (2.13% to 2.66%), fat content (24.2% to 30.7%) and total dietary fiber content (1.83 g/100g to 4.70 g/100g) in biscuits increased when the level of BPF substitution increased. The texture analysis demonstrated that BPF-containing biscuits had significantly higher value in hardness (1071.15 to 1300.61g) than control biscuit (992.69 g). Ä°n contrast, the study showed a significant decrease in fracturability, lightness, width and height as the concentration of BPF increased. Sensory evaluation indicated that biscuit incorporated with BPF up to 20% level did not affect the appearance, taste, texture and overall acceptability ratings by the panelists. Ä°n conclusion, BPF can be used as a functional ingredient and partially substituted wheat flour in biscuit production.Â